GREED IN JEANNE DUPRAU’S NOVEL THE CITY OF EMBER - Wanda Prayoga Ilyas; Purwarno Purwarno (JOURNAL OF LANGUAGE, 2019)
This study is the result of a library research which is qualitative in nature on the greed for power and for food of the antagonist named Cole depicted in Jeanne DuPrau’s The City of Ember. Some definitions as well as concept about the antagonist and greed from the various sources are generated in chapter two to bring about the proper arguments and ideas related to the analysis of the topic. The method used in analyzing the data in this paper is Descriptive Qualitative Research in which it is a research method used to acquire and describe accurate, factual, and systematic data. The findings show that Cole, as a mayor in the city of Ember who is supposed to protect his citizens in the city of Ember, has misused his power to dupe his citizens. He convicingly says to the citizens that if they work hard and dedicate their life to the city of Ember, the city will be prosperous. In fact, he speaks so glibly to the citizens for the shake of his own interests that he will not need to work hard anymore to control the city. Mayor Cole is also a very greedy man. So greedy he is that he has ordered two of his trusted workers named Looper and Lizzie Bisco to steal the food supplies from the storeroom and hiden them in a tunnel pipeworks, called the room 351 to be enjoyed by himself. He has overabundance of food while the citizens of Ember are in a crisis of food. Furthermore, the finding of this study shows that Mayor Cole’s evil deeds is revealed by Doon and Lina in the long run.